The Future of ACP-EU relations post-2020 : an overview of relevant analysis by ECDPM. Version 1 (ECDPM MaastrichtNL, 2014)
Brings together summaries of selected ECDPM resources relevant to the future of ACP-EU relations and the Cotonou Partnership Agreement post-2020.
Keywords: PARTNERSHIP